Macroeconomic Policies and Long-Term Growth : A Conceptual and Empirical Review - Villanueva, Delano; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 1991)
This paper reviews the theoretical and empirical aspects of the relationship between macroeconomic policies and the long-run rate of growth of GNP. The macroeconomic policies examined include fiscal policies, monetary and interest rate policies, external policies, and policies to reform the goods and labor markets, including adjustments of producer prices and wages. In general, the effects of these policies on growth operate directly or indirectly through their influence on investment in physical and human capital, and on factor productivity. The available empirical evidence confirms the effects of specific macroeconomic and financial policies on long-run growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet